Evaluating the expression of miRNAs in the culture medium of human embryos with normal sex chromosomes and embryos with an X sex chromosome (Turner syndrome) - Shahrzad Aghajani; Ali Salehzadeh; Fatemeh Ghasemian; Marzieh Mehrafza (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Īlām, 2023)
Introduction: Assisted reproductive techniques and Preimplantation Genetic Test (PGT) are performed to detect aneuploidy to achieve a euploid baby's birth in infertile or low-fertility couples. miRNAs are single-stranded, non-coding RNA molecules and essential regulators of gene expression in various biological and physiological processes. The present study aimed to investigate some miRNAs damaged in the culture media of human embryos (as diagnostic biomarkers) and their relationship with the degree of aneuploidy of the embryo and assisted reproductive methods. Material & Methods: The PGT cycles derived sperm intracytoplasmic injection (April 2021 to June 2021) were evaluated using fluorescence in situ hybridization (FISH). Following that, the culture medium of three euploids and three aneuploid embryos with an X sex chromosome (Turner) was collected and the expression of has-miR-199a-5p, has-miR-199b-3p has-miR-379-5p, has-miR-483-5p, has-miR-99a-5p, and has-miR-432-5p were investigated using quantitative reverse transcription polymerase chain reaction (RT-qPCR). Findings: In the culture medium of euploid embryos, a significant increase was observed in the expression of three miRNAs, including hsa-miR-379-5p, hsa-miR-199a-5p, hsa-miR-199b-3p. Moreover, a decrease was detected in the expression of three miRNAs, including hsa-miR-432-5p, hsa -miR-483-5p, and hsa-miR-99a-5p, with a significant difference (P<0.0001). The expression of these miRNAs in the culture medium of Turner embryos with the model was the opposite. Discussion & Conclusion: In examining the expression level of miRNAs investigated in this project, the increase in the expression of three miRNAs and the decrease in the expression of three other miRNAs in euploid embryos demonstrated the opposite expression pattern of the same miRNAs in Turner embryos. These results can be considered promising for using non-invasive methods instead of fetal biopsy in the diagnostic studies of the number of sex chromosomes.